A critical discourse analysis of the representation of the opposition parties in the 2008 Malaysian general election in Malaysian print media - Inayatun Nimah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2009)
The study was conducted to investigate the representation of the opposition parties in the twelfth Malaysian general election in the Malaysian print media. The data for the analysis has been gathered from two widely-read local newspapers written in English The Star and The New Straits Times. 40 articles were selected from the newspapers two weeks before and two weeks after the polling day which was on March 8, 2008. Only news reported or related to the opposition parties was selected as data for the study. The basic premise of the study is that news is constructed; it is not a reflection of reality. The study aims to help increase readers’ awareness in reading and thinking critically. The study is limited to analyzing data on the lexicogrammar level and made use of three analytic tools for its data analysis transitivity system, modality and thematic structure. The study revealed that the print media made use of some linguistic items to represent the opposition parties. The print media represented and constructed the opposition image and identity through language use and directed readers to a particular point of view.